Bone- and Antler-Working at Silchester: Evidence from Early Excavations. (14th July 2015) - Bacon, Joanna; Crummy, Nina
Abstract Craft debris and finished artefacts in Reading Museum's Silchester Collection are used alongside current understanding of Romano-British urban intensive carcass processing and object assemblages to re-assess the evidence for bone- and antler-working in the town over that period.